Highly flexible and mechanically strong polyaniline nanostructure @ aramid nanofiber films for free-standing supercapacitor electrodes. Issue 9 (24th February 2020) - Yin, Qing; Jia, Hongbing; Mohamed, Amel; Ji, Qingmin; Hong, Liu
Abstract : The excellent integration of high specific capacitance and superior mechanical properties for flexible electrode can be achieved by the combination of aramid nanofiber and polyaniline. Abstract : A key challenge for the fabrication of flexible electrochemical capacitors is to prepare robust electrode materials with excellent integration of high specific capacitances and superior mechanical properties. Aramid nanofibers (ANFs) are emerging candidates for constructing flexible electrode materials due to their superior mechanical properties. However, the present ANF based electrode materials are generally designed by mixing ANFs with electrochemically active components, which results in an unfavorable trade-off in mechanical and electrochemical properties. In this work, we reported flexible, mechanically strong, and free-standing supercapacitor electrodes based on polyaniline (PANI) nanostructure functionalized ANF films for the first time. The flexible PANI@ANF film electrodes achieved an efficient combination of mechanical and electrochemical performance in a single platform with a specific capacitance of 441.0 F g −1 at a current density of 1 A g −1 and a tensile strength of 233.3 MPa, respectively. This kind of free-standing electrode material may have great potential in the development of flexible energy-storage devices. Furthermore, we anticipate that this study may provide insight into the functionalization of aramid nanofiber-based materials for structural energy and power systems with high mechanical performance.